Potensi Air Perasan Batang Bayam Merah (Amaranthus Tricolor L) Sebagai Alternatif Pewarnaan Telur Cacing Soil Transmitted Helminth - Artanti, Lina Yunda; Sungkawa, Hendra Budi; Djohan, Herlinda; Nuswantoro, Ari; Alfianita, Riska (Universitas Pahlawan Tuanku Tambusai, 2024)
in the examination of worm eggs uses 2% eosin. However, eosin has shortcomings because it is not easily decomposed, so an alternative coloring that is more environmentally friendly is needed. Red spinach plants have the potential to be used as a natural dye because they contain anthocyanin compounds. This study aims to determine the potential of red spinach stem juice (amaranthus tricolor L) as an alternative to staining soil transmitted helminth eggs. Research design of quasi experiment with purposive sampling technique. Samples used red spinach stem juice (amaranthus tricolor L) in a ratio of 1:1, 1:2, 1:3, 1:4, and 1:5 by direct method and repeated 5 times. Based on the results of the research, the juice of red spinach stems in the ratio of 1:1 showed 60% results, the ratio of 1:2 showed 53% results, the ratio of 1:3 showed 53% results, the ratio of 1:4 showed 40% results and the ratio of 1:5 showed 40% results. The conclusion of this study is that the concentration of 1: 1 has the highest quality which is considered to have potential as an alternative coloring.